Conformational and vibrational analysis of methyl methanesulfonate, CH3SO2OCH3 - Tuttolomondo, María Eugenia (2009)
The molecular structure of methyl methanesulfonate, CH3SO 2OCH3, has been optimized by using methods based on density functional theory, coupled cluster, and Moller-Plesset second order perturbation theory (MP2). With regard to CH3SO2OCH 3, two populated conformations with symmetries Cs and C1 are obtained, the former being more stable than the latter. The theoretical data indicate that although both anti and gauche conformers are possible by rotation about the S-O bond, the preferred conformation is anti. The total energy as a function of the CSOC dihedral angle has been calculated using the MP2 method with the 6-31G(d) and cc-pVDZ basis sets and the hybrid functional B3LYP using 6-31G(d), 6-311G(d,p), and 6-311++G(d,p) basis sets. A natural bond orbital analysis showed that the lone pair →σ * hyperconjugative interactions favor the anti conformation. Furthermore, the infrared spectra for the liquid and solid phases, the Raman spectrum for the liquid one, and the inelastic neutron scattering spectrum of the solid phase have been recorded, and the observed bands have been assigned to the vibrational modes. The experimental vibrational data, along with calculated theoretical force constants, were used to define a scaled quantum mechanical force field for the target system that enabled us to fit the measured frequencies with a final root-mean-square deviation of 10 cm-1.